Occurrence of Free d-Amino Acids and Aspartate Racemases in Hyperthermophilic Archaea - Matsumoto, Megumi (American Society for Microbiology, 1999)
The occurrence of free d-amino acids and aspartate racemases in several hyperthermophilic archaea was investigated. Aspartic acid in all the hyperthermophilic archaea was highly racemized. The ratio of d-aspartic acid to total aspartic acid was in the range of 43.0 to 49.1%. The crude extracts of the hyperthermophiles exhibited aspartate racemase activity at 70°C, and aspartate racemase homologous genes in them were identified by PCR. d-Enantiomers of other amino acids (alanine, leucine, phenylalanine, and lysine) in Thermococcus strains were also detected. Some of them might be by-products of aspartate racemase. It is proven that d-amino acids are produced in some hyperthermophilic archaea, although their function is unknown.